In vitro efficacy of a non‐instrumentation technique to remove intracanal multispecies biofilm. (8th March 2022) - Ordinola‐Zapata, Ronald; Mansour, Dina; Saavedra, Flavia; Staley, Christopher; Chen, Ruoqiong; Fok, Alex S.
Abstract: Aim: The aim of this study was to assess the efficacy of a non‐instrumentation technique to disinfect root canals infected by a human dental plaque‐derived multispecies biofilm. Methodology: Twenty‐two mandibular incisors were accessed, autoclaved and inoculated with dental plaque. The Center for Disease Control biofilm reactor was used to promote contamination of the root canal space. In the conventional technique (control), the specimens were instrumented until size 35/04 and irrigated with 6% NaOCl. In the non‐instrumentation technique, a glide path was established using K‐files size 10–20 and specimens were immediately cleaned with the GentleWave System. Samples were obtained for culture and 16S rRNA gene sequencing. Differences in abundances of genera were evaluated using Kruskal–Wallis test, and differences in alpha diversity were compared using anova . Alpha and beta diversity indices were calculated using mothur. The Shannon and Chao1 indices were used to measure alpha diversity. The Bray–Curtis dissimilarity was used to measure beta diversity. Differences in community composition were evaluated using analysis of similarity with Bonferroni correction for multiple comparisons. Results: The total numbers of reads in biological samples ranged from 126 to 45 286. Significantly fewer reads were obtained from samples following cleaning by either method ( p < .0001), and significantly fewer reads were obtained in post‐cleaning samples following conventional versus non‐instrumentation cleaning regiment ( p = .002). Communities in pre‐treatment samples were similar in both groups; however, significantly greater relative abundances of Streptococcus, Veillonella and Campylobacter were observed following cleaning using non‐instrumentation technique (Kruskal–Wallis p = .009, .033, and .001, respectively). Whilst no significant differences were observed in Shannon alpha diversity, the Chao1 index was significantly lower in post‐cleaning samples. Conclusions: Significant shifts in composition were observed following cleaning by using both regimens, but the impact of this change was greater following a conventional cleaning technique.